PEMANFAATAN MEDIA VIDEO ANIMASI JARI CENTINI (REMAJA PUTRI CEGAH STUNTING SEJAK DINI) SEBAGAI MEDIA EDUKASI PENCEGAHAN STUNTING - Diana, Helmi; Wiwin Mintarsih Purnamasari (Poltekkes Kemenkes Tasikmalaya, 2025)
Stunting has an impact that affects the child's future if prevention is not carried out early. Adolescents are a group that has a large role in producing offspring in the future. Lack of knowledge of adolescents about stunting is a factor causing the high rate of stunting, educational media that can be easily understood by adolescents is animated videos. The purpose of this community service is to increase knowledge about preventing stunting in adolescents. The activities carried out were in the form of education, using CENTINI educational videos, conducting HB, TB, BB level checks on adolescent girls, making a form for filling out a compliance monitoring sheet for consuming FE tablets. The method used was socialization and health education to adolescent girls through videos and explanations of the FE calendar which were distributed to all respondents. The location of the activity was SMPN 9 Kota Tasikmalaya. The stages of the activity include the stages of preparation, implementation and reporting. Data from the results of community service activities showed an increase in the capacity of adolescent girls, showing a change of 22 points in the pre-post test education, HB level checks from 30 people. The adolescent girls who were examined who had anemia were 16 people (53%) and 14 people did not have anemia. All teenagers showed high enthusiasm for this activity and hoped that educational activities on stunting and nutritional status could be carried out sustainably to improve the fitness and health of adolescent girls.